ASSESSING NURSING INTERNS PERCEPTION REGARDING THEIR CLINICAL INTERNSHIP AMONG PRIVATE NURSING COLLEGES OF LAHORE, PUNJAB (Journal of Medical & Health Sciences Review, 2025)
Background: Nursing internship is a practical experience program designed for nursing students to gain hands-on experience in a health care setting. As nursing interns enter in a most challenging hospital environment, so there is a crucial need to assess their perception during their internship period which influence evidence-based practice and quality patient care.Objective: To assess the perception of nursing interns regarding their clinical internship in private nursing colleges of Lahore, Punjab.Methodology: Descriptive cross-sectional research design was used to assess the perception of nursing interns.Setting: Study was conducted at Fatima Memorial Hospital and Ittefaq Hospital Lahore.Sampling technique: Random sampling technique was used.Results: According to the results 57.6% of the nursing interns have moderate level of perception regarding their clinical internship. Similarly, 36.4% have high level of perception. However, 6.1% of interns have low level of perception. In the same way 37.9% of interns are confident in managing patient care assignment. However, 69.6% of nursing interns don`t feel confident in managing the care of more than three to four patients.Conclusion: It was concluded that there is a strong relationship between perception of nursing interns and quality patient care. High level of perception helps the nursing interns to provide competent care.